PENGARUH BLENDED LEARNING DALAM MENINGKATKAN EFEKTIFITAS PEMBELAJARAN - Alifa Amalia Izzati; Unik Salsabila Hanifah; Safira Anggraeni; Nurul Azizah; Dhuha Fitri Nur Rohmah (JURNAL EDUSCIENCE (JES), 2021)
Blended learning is a new thing in Indonesia. When the covid-19 hit all corners of the world, various activities became paralyzed. So, the goverment requires to reduce and even eliminate face-to-face activities.blended learning is considered very appropriate and very effective to maximize learning in the time of the covid-19 pandemic. The existence od this writing is intended to find out te influence of blended learning in improving the effectiveness of learning. The writing of this journal uses quantitative research methods through a case study approach that is relevant to today’s life. This research is descriptive and analyzes some of the existing information. Data collection is done by discussing groups by finding and analyzing information by collecting secondary data from various sources such as books, journals, scientific literature articles and online mass media reports that present data based on relevant literature. Because this activity is a combination of offline participants and online participants, various techniques and tactics must be possessed by the teacher so that this learning runs effectively and as expected.Keywords: Pandemic, blended learning, effectivity